PENGARUH MODEL FRAYER MELALUI PENGUASAAN KOSAKATA SISWA KELAS V SEKOLAH DASAR (JS (JURNAL SEKOLAH), 2021)
Abstract: The problem in this research is is there any influence of the Frayer model through the vocabulary mastery of fifth grade elementary school students?. The research method used is an experimental research method. The population and sample in this study were all fifth grade students of SD Negeri 10 Sembawa, totaling 23 students. Data collection techniques in this study using tests and documentation. The data analysis technique used is a simple linear regression equation with hypothesis testing using the Mann-Whitney U Test (non-parametric statistics). The results showed that there was an influence of the Frayer model through the vocabulary mastery of fifth grade elementary school students. This is proven by the analysis of the Mann-Whitney U Test with the Asymp value. Sig. (2-tailed) or p value of 0.016 < 0.05. If the p value < critical limit 0.05; then there is the influence of the Frayer model through the vocabulary mastery of fifth grade elementary school students or which means Ha is accepted.Keywords: Frayer model, vocabulary.Abstrak: Masalah dalam penelitian ini adalah adakah pengaruh model Frayer melalui penguasaan kosakata siswa kelas V sekolah dasar?. Metode penelitian yang digunakan adalah metode penelitian eksperimen. Populasi dan sampel dalam penelitian ini adalah seluruh siswa kelas V SD Negeri 10 Sembawa yang berjumlah 23 orang siswa. Teknik pengumpulan data dalam penelitian ini menggunakan tes dan dokumentasi. Teknik analisis data yang digunakan adalah persamaan regresi linier sederhana dengan uji hipotesis menggunakan Uji Mann-Whitney U Test (statistik non parametris). Hasil penelitian menunjukkan bahwa ada pengaruh model Frayer melalui penguasaan kosakata siswa kelas V sekolah dasar. Hal tersebut terbukti dengan analisis Uji Mann-Whitney U Test dengan nilai Asymp. Sig. (2-tailed) atau p value sebesar 0,016 < 0,05. Apabila nilai p value < batas kritis 0,05; maka ada pengaruh model Frayer melalui penguasaan kosakata siswa kelas V sekolah dasar atau yang berarti Ha diterima.Kata kunci: model frayer, kosakata.